USING DISPOSABLE DIAPERS AS POSSIBLE WAY TO PREVENT INFANT DIAPER DERMATITIS - E.A. Vishneva; L.S. Namazova; M.E. Ivardava (Union of pediatricians of Russia, 2008)
Currently the Russian market offers a wide assortment of baby diapers which often makes choice hard. The authors provide complete information on the essential quality criteria for this product in terms of medicine. After reading this article pediatricians will be able to teach parents how to «recognize» premium-class diapers that are optimal for their babies, and how to use them properly.Key words: diapers, usage, characteristic, children.